2007
DOI: 10.1248/cpb.55.829
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Intramolecular Ring Closure of Aminoalcohols with Diethyl Carbonate to Oxazolidinones

Abstract: In connection with our interest in the chemistry of baminoalanines, [1][2][3][4] we have reported the synthetic application of these materials as a synthon for the preparation of a 5-membered oxazolidinone ring system.2) Some of the oxazolidinone derivatives have attracted much attention not only as a synthetic target but also because of the importance of the related compounds in the biological activities. 5,6) This paper deals with the relative rates of ring closure by cyclization with diethyl carbonate (EtO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…2,[25][26][27][28][29] Recently the synthesis of 1,3-oxazolidin-2-one by the reaction of 1,2-amino alcohols with dimethyl carbonate in presence of phosphazene base was reported. 30 Here we report a simple and efficient synthesis of the 3,5-substituted oxazolidin-2-ones containing vinyloxyalkyl moiety 2 from 1-alkylamino-and 1-arylamino-3-[2-(vinyloxy)ethoxy]-2-propanols (1) and dimethyl carbonate (DMC) in the presence of readily available inexpensive bases (sodium methoxide or metallic sodium).…”
Section: Introductionmentioning
confidence: 99%
“…2,[25][26][27][28][29] Recently the synthesis of 1,3-oxazolidin-2-one by the reaction of 1,2-amino alcohols with dimethyl carbonate in presence of phosphazene base was reported. 30 Here we report a simple and efficient synthesis of the 3,5-substituted oxazolidin-2-ones containing vinyloxyalkyl moiety 2 from 1-alkylamino-and 1-arylamino-3-[2-(vinyloxy)ethoxy]-2-propanols (1) and dimethyl carbonate (DMC) in the presence of readily available inexpensive bases (sodium methoxide or metallic sodium).…”
Section: Introductionmentioning
confidence: 99%
“…1,2) Some of the synthesized compounds were evaluated for antibacterial activity with gram-negative (Escherichia coli) and gram-positive (Staphylococcus aureus) strains, and we found that most of the 4-dialkylaminomethyloxazolidinone-related derivatives (A) 1) showed no significant antibacterial activities against either gram-positive or gram-negative strains. Therefore, we carried out further molecular modification of linezolid to the hydantoin analogue (B).…”
mentioning
confidence: 98%
“…Synthesis of 5-Dialkylaminomethyl-3-aryl-hydantoins (3) and Related Compounds In our synthetic studies on b-aminoalanines (1), 9) we have already reported target molecules of 5-dialkylaminomethyl-3-aryl-hydantoins (3) which are easily prepared by cyclization of urea derivatives (2) readily obtained by addition of b-aminoalanines to arylisocyanates (or arylisothiocyanates). 10,11) The hydantoin derivatives (3) described in this paper were prepared in a manner similar to that reported previously.…”
mentioning
confidence: 99%